Sexism and Gender: Differences in Slang Terms in Icelandic and English as a Second Language - Sigríður Gyða Héðinsdóttir 1987- (2014)
Research on gender inequality in language has been prominent since the structured study of sexism in language first received attention as the result of the feminist movement in the 60s and 70s. Since then, numerous studies have been conducted on the topic of language and gender. This thesis reports on a study which duplicates and extends a study by Grossman and Tucker (1997) concerning the sexual and derogatory connotations of slang words for men and women in English. Here sexism and gender differences were investigated in the lexical knowledge of Icelandic speakers of Icelandic and English as a second language. Twenty female and twenty male students in political sciences at the University of Iceland reported all the slang terms they knew to describe either the target word “kona” (e. woman) or “maður” (e. man). Twenty female and fourteen male students in English at the University of Iceland were asked to do the same for the target words “woman” and “man”. The terms were then rated as sexual or derogatory. It was hypothesized that more derogatory and sexual slang terms would be listed in English due to studies showing that bilingual individuals tend to convert to a second language when using taboo or vulgar words. The results show that more terms were listed for female target words in both Icelandic and English and overall, more terms were listed in English than Icelandic. More sexual words were listed for female target words in English than in Icelandic, which is in agreement with the hypothesis. Results indicate that there are more sexual and derogatory terms that describe women and that the feminist language reform has not had an impact on slang.